(untitled) (CR. Conservación y Restauración, 2025)
Based on a diagnosis generated by the personnel of the National Documentary Heritage Conservation Program (PNCAD) of the Coordinación Nacional de Conservación del Patrimonio Cultural (CNCPC) of the Instituto Nacional de Antropología e Historia (INAH), regarding the problem of theft and illicit trafficking, it was concluded that in order to combat it, it is important to do it from the root, that is, by doing it from inside of the collections together with the staff who work in them. That is important because these are the places where the main output and documentary theft is generated and, consequently, where they are trafficked. Those in charge of the collections then become responsible for practicing actions that help to prevent, or at least reduce, that situation. In this regard, the PNCAD, within its lines of work and through the Training course on conservation of documentary collections, trains and provides various theoretical tools, such as the session on the problems and prevention theft and illicit trafficking in documentary collections.